Exploring the amyloid proteome in immunoglobulin‐derived lymph node amyloidosis using laser microdissection/tandem mass spectrometry. Issue 7 (30th May 2013) - D'Souza, Anita; Theis, Jason; Quint, Patrick; Kyle, Robert; Gertz, Morie; Zeldenrust, Steven; Vrana, Julie; Dogan, Ahmet; Dispenzieri, Angela
<x xml:space="preserve">Abstract</x> Amyloidosis affecting lymph nodes (LN) may occur in the setting of systemic amyloidosis or as an entity localized to the site of production (peritumoral). Why some LN amyloid remains peritumoral is unknown. We speculated that the composition of amyloid in these two presentations differs. We analyzed the amyloid proteome in LN amyloid samples to identify differences between the systemic and peritumoral subtypes. In immunoglobulin‐derived LN amyloidosis (N = 26), 70% had heavy chain amyloid (AH or mixed AH/AL). True localized LN amyloidosis was rare, with only 2 patients without a monoclonal protein component. Nineteen patients (73%) had typical amyloid syndromes (100% of AL vs 67% of AH/AL, P = 0.02). A trend to improved survival for the AH/AL group in comparison to AL (median 5‐year survival 48 vs. 19 months, P = 0.06) was seen. Mass spectrometric amyloid analysis is a powerful tool for characterizing amyloid and may provide additional prognostic information. Am. J. Hematol. 88:577–580, 2013. © 2013 Wiley Periodicals, Inc.